Peran Pendidikan Perempuan Muslim dalam Transformasi Nasional untuk Pembangunan Sumber Daya Manusia - Alkanchi, Hassan Malami; Ahmad, Nura; Yusof, Yusmini Binti Md; Zaidan, Ashraf Mohammad (Program Pascasarjana UNU Surakarta, 2024)
The significance of Muslim women's education in Islam for national transformation cannot be underestimated. Islam places a great focus on the role and empowerment of women, and Muslim women play a crucial part in shaping a nation's social, political, and economic landscape. Through their adherence to Islamic principles and values, Muslim women contribute to the development and progress of their respective countries. Their involvement in education, entrepreneurship, and community leadership helps to drive economic growth and social cohesion. It has been widely recognized that educated women are key contributors to the growth and development of society. The paper is purely theoretical in nature; it used a literature search of online published articles and an available database to gather the data. Secondary data was used as a major source for gathering information. The paper analytically discusses the emerging themes about women's education role in national transformation for human development. Findings revealed that empowering women through education can promote overall societal development Therefore, investing in the education of Muslim women is not only essential for national human development but also for national transformation. Furthermore, the findings of the paper revealed that the education of Muslim women is critical for the progress and prosperity of a nation. Study findings confirmed that women’s education has a significant impact on individuals and societal development in transformation for national development and capacity building for effective human development.